Role of Valgus Osteotomy and fixation with Double Angle Blade Plate in the management of Neglected and Ununited femoral neck fracture in young patients - Hari Om Agarwal; Sanjeev Sreen; Manjit Singh; Ayush Kumar Jain; Sanjeev Arora (GMC Patiala Journal of Research and Medical Education, 2019)
Background: Non-union of femoral neck fracture in young patients is still a problem as they are too young to have hip replacement and other salvage procedures are usually unsatisfactory. Pauwels described valgus osteotomy for nonunion of femoral neck which was used by later surgeons also. Methods: We report a series of 20 patients of nonunion of femoral neck fracture which were taken up for valgus osteotomy and fixed with 120° double angled blade plate. Average age of patients was 35 years. Delay in presentation ranged from 8weeks-58weeks (mean 24weeks). Average follow up was 18 months (12 months to 36 months). Results: Femoral neck fractures united in 18 patients (90%). Excellent to good results were seen in 70% patients. Conclusion: 120° double angled blade plate provides rigid internal fixation after valgus osteotomy and being a more familiar fixation device simplifies the procedure and gives good results.